On the size of tokamak fusion power plants. (4th February 2019) - Zohm, Hartmut
Abstract : Figures of merit for future tokamak fusion power plants (FPPs) are presented. It is argued that extrapolation from present-day experiments to proposed FPPs must follow a consistent development path, demonstrating the largest required leaps in intermediate devices to allow safe extrapolation to an FPP. This concerns both plasma physics and technology. At constant plasma parameters, the figures of merit depend on both major radius R and magnetic field B . We propose to use the term 'size' for a combination of R and B to avoid ambiguities in scaling arguments. Two routes to FPPs are discussed: the more conventional one increasing R, based on the assumption that B is limited by present technology; and an alternative approach assuming the availability of new technology for superconducting coils, allowing higher B . It is shown that the latter will lead to more compact devices, and, assuming a criterion based on divertor impurity concentration, is in addition more favourable concerning the exhaust problem. However, in order to obtain attractive steady-state tokamak FPPs, the required plasma parameters still require considerable progress with respect to present experiments. A credible strategy to arrive at these must hence be shown for both paths. In addition, the high-field path needs a demonstration of the critical technology items early on. This article is part of a discussion meeting issue 'Fusion energy using tokamaks: can development be accelerated?'.